Trust in financial services: the influence of demographics and dispositional characteristics - Moin, S.M.A.; Devlin, James; McKechnie, Sally (Palgrave Macmillan, 2017)
So far, very little attention has been paid to examining consumer perceptions of trust from an interdisciplinary perspective. The purpose of this study is to examine how consumer trusting belief and disposition to trust within the financial services sector vary on the basis of individual demographic differences in trust. The research provides new insights into how consumers with higher dispositional trust have higher institutional trust and higher trusting belief and how consumers’ trusting belief significantly differs according to their demographic background in terms of age, marital status, ethnicity and gross annual income. The findings offer useful insights for the managers in financial institutions to carefully consider the impact of the influence of these individual differences on consumer behaviour in order to serve the needs of consumers in their target market and be able to design financial products and develop trust building strategies to attract and retain them. They also call for the action of the regulators and the financial institutions to play their part in building strong institutional systems that contribute to engendering higher levels of consumer trust.